Short-term application of diquafosol ophthalmic solution benefits children with dry eye wearing orthokeratology lens - Yuanfang Yang; Yuanfang Yang; Yuanfang Yang; Yuanfang Yang; Qinghui Wu; Yao Tang; Haoran Wu; Zhiwei Luo; Wenyu Gao; Ziqi Hu; Lijun Hou; Min Wang; et al. (Frontiers in Medicine, 2023)
PurposeThis aim of this study was to evaluate the effect of 3% Diquafosol Ophthalmic Solution (DQS) on children with dry eye from wearing overnight orthokeratology (OrthoK) lenses.MethodsMyopic children aged 8–18 years with dry eye syndrome were enrolled in this prospective observational study, and they were grouped according to their OrthoK treatment history for at least 1 year. All participants received DQS 4 times per day for 1 month. The following indicators were measured at baseline 1 month after treatment: the Dry Eye Questionnaire-5 (DEQ-5), non-invasive tear meniscus height (TMH), non-invasive tear film break-up time (first and average, NIBUT-F and NIBUT-A), meibomian gland score (MG score), conjunctival hyperemia redness score (R-scan), and blink pattern analysis.ResultsA total of 104 participants (189 eyes) including 40 OrthoK wearers (72 eyes) and 64 Orthok candidates (117 eyes) completed the study. Of all, after DQS treatment for 1 month, DEQ-5 scores reduced from 5.54 ± 3.25 to 3.85 ± 2.98 (t = −3.36, p = 0.00). TMH increased from 0.20 ± 0.05 mm to 0.21 ± 0.05 mm (t = 2.59, p = 0.01), NIBUT-F and NIBUT-A were prolonged from 6.67 ± 4.71 s to 10.32 ± 6.19 s and from 8.86 ± 5.25 s to 13.30 ± 6.03 s (all p = 0.00), respectively. R-scan decreased from 0.69 ± 0.28 to 0.50 ± 0.25 (t = −9.01, p = 0.00). Upper MG scores decreased from 1.04 ± 0.32 to 0.97 ± 0.36 (t = −2.14, p = 0.03). Lower MG scores, partial blink rate, partial blinks, and total blinks did not change significantly. Both break-up time (BUT) and R-scan improved significantly after DQS treatment for 1 month (all p = 0.00) in OrthoK candidates and OrthoK wearers. Among the OrthoK wearers, TMH and dry eye symptoms increased significantly (all p = 0.00) but did not increase in OrthoK candidates (p > 0.05). There were no adverse events related to DQS.ConclusionDiquafosol Ophthalmic Solution was effective for children wearing overnight orthokeratology in relieving dry eye symptoms and improving ocular surface parameters, which may help improve children's OrthoK wearing tolerance and compliance.